The factors that influence on adoption of cloud computing for small and medium enterprises - Amini, Mahyar (2014)
Cloud computing has emerged as one of the most discussed topics among enterprise information technology (IT) professionals. Small and medium enterprises (SMEs) with low budget and human resources are one of the major groups that tend to use cloud computing for achieving the benefit of this technology. A multitude of factors influence the adoption of cloud computing for SMEs. These decisive factors must be systematically evaluated prior to making the decision to adopt cloud-based solutions. The purpose of this study is to identify these factors and determine the extent to which they influence the adoption of cloud computing for SMEs. Therefore, the project describes a research model that is based on the diffusion of innovation (DOI) theory and the technology, organization and environment (TOE) framework. Based on previous study, research model was developed to test eight (8) variables, which are: relative advantage, compatibility, security concerns, cost savings, technology readiness, top manager support, competitive pressure and regulatory support. Data was collected by survey questionnaires from a sample of 22 SMEs that all of these SMEs as a customer’s of one cloud provider. There are 77 experts in information technology department from those SMEs are selected to fill the questionnaires. The Smart PLS tool was used for data analysis. The results of the data analysis generally support the model, as well as all of the proposed hypotheses. In summary, the results of this research have shown relative advantage, compatibility, security concerns, cost savings, technology readiness, top manager support, competitive pressure and regulatory support were found to have significant influence on adoption of cloud computing for SMEs